2004
DOI: 10.2166/wst.2004.0291
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of persistent DOC in municipal WWTP effluent for groundwater recharge

Abstract: Groundwater recharge is becoming common in areas where the withdrawal of groundwater exceeds its natural recharge. Wastewater treatment plant (WWTP) effluent can be used for this purpose, but persistent organic compounds can only be partly removed during soil passage. This point was confirmed in degradation tests using soil columns in which the DOC of a membrane bioreactor (MBR) permeate could only be reduced by 15% and adsorbable organic iodine (AOI) by 2%. However, ozonation was found to improve biodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Results from this study confirmed that the combination of ozonation and SAT provides a good way to benefit from this effect. A significant reduction in DOC following a treatment combining ozonation and sand columns was also demonstrated by Schumacher et al (2004).…”
Section: Short Satmentioning
confidence: 80%
See 1 more Smart Citation
“…Results from this study confirmed that the combination of ozonation and SAT provides a good way to benefit from this effect. A significant reduction in DOC following a treatment combining ozonation and sand columns was also demonstrated by Schumacher et al (2004).…”
Section: Short Satmentioning
confidence: 80%
“…Ozonation followed by soil columns to simulate the SAT process (Schumacher et al, 2004;Tiwari et al, 2014), quick biological sand filtration (Hollender et al, 2009) or biological activated carbon (BAC) treatment (Gerrity et al, 2011;Reungoat et al, 2012) demonstrated improved biodegradation of DOC and elimination of ozonation byproducts and TrOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Siddiqui et al, 1997;Trequer et al, 2010;Yavich et al, 2004). Experiments with permeate from a membrane bioreactor and sand columns to simulate artificial groundwater recharge showed an improvement of DOC reduction from 15% to 61% by applying 1.9 mg O 3 /mg DOC (Schumacher et al, 2004). Thus, a combination of oxidation technologies using ozone with the natural degradation capacity of a subsurface passage could help to ensure the drinking water production under changing climate and hydraulic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ozonation has a good effect on the oxidation of refractory contaminants, due to its higher oxidation potential and the formed secondary oxidant, hydroxyl radicals (OH • ) [4]. Most of the studies concerning the ozonation of CPs are focused on the degradation levels or the identification of some reaction by-products [5][6][7].…”
Section: Introductionmentioning
confidence: 99%